1993
DOI: 10.1159/000133479
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the human gene for pregnancy-associated plasma protein A (PAPPA) to 9q33.1 by fluorescence in situ hybridization to mitotic and meiotic chromosomes

Abstract: Low levels of pregnancy-associated plasma protein A (PAPPA) during the first trimester has been suggested as a biochemical indicator of pregnancies with aneuploid fetuses. Furthermore, the complete absence of PAPPA in pregnancies associated with Cornelia de Lange syndrome (CL) has suggested a causal connection between PAPPA and the development of CL. We have assigned the locus for PAPPA to chromosome region 9q33.1 on mitotic and meiotic chromosomes by fluorescence in situ hybridization, using a 3.7-kb partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
0
17
0
4
Order By: Relevance
“…PAPPA has previously been localized to human chromosome 9q32-33, a region associated with a high frequency of LOH in ovarian tumors (Silahtaroglu et al, 1993;Schultz et al, 1995). In addition, the 9q32 band contains the FRA9E CFS; hence, we were interested in the genomic position of PAPPA relative to this region of instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAPPA has previously been localized to human chromosome 9q32-33, a region associated with a high frequency of LOH in ovarian tumors (Silahtaroglu et al, 1993;Schultz et al, 1995). In addition, the 9q32 band contains the FRA9E CFS; hence, we were interested in the genomic position of PAPPA relative to this region of instability.…”
Section: Discussionmentioning
confidence: 99%
“…Partial sequence from PAPPA was recovered from this technique because of its presence in OSE, but absence from some of the cancer cell lines. A previous report had mapped PAPPA to 9q33.1, possibly close to FRA9E (9q32) (Silahtaroglu et al, 1993). Consequently, we selected two overlapping BACs, which together contained the entirety of the PAPPA genomic sequence, and performed fluorescence in situ hybridization (FISH) on APC-induced chromosomes.…”
Section: Cloning and Characterization Of Fra9ementioning
confidence: 99%
See 1 more Smart Citation
“…The structural gene for PAPP-A has been localized to the long arm of chromosome 9 (band 9q33.1) (Silahtaroglu et al, 1993) and has been cloned (Kristensen et al, 1994). Ireland et al (1991) have suggested that the gene for CdLS may map to the long arm of chromosome 3 at position 3q26.3, based on the study of an infant with classical CdLS and absent hands and forearms who was found on chromosome analysis to have a de novo translocation t(3;17)(q26.3:q23.1).…”
Section: Discussionmentioning
confidence: 99%
“…The gene for PAPP-A in humans is located on chromosome 9q33.1 (18) , spans over 200 kb of DNA, and contains 22 exons with a length from 72 to 1063 nucleotides separated by 21 introns of various length (19) . PAPP-A is synthesized as a 1627-residue precursor preproprotein with a 22-residue putative signal peptide and a propeptide of 58 residues, so that the mature protein then contains 1547 amino acids.…”
Section: Biology Of Papp-a: Gene Structure and Functionmentioning
confidence: 99%